Evaluating alternative DaaS solutions in private and public OpenStack Clouds. (24th March 2017) - Celesti, Antonio; Mulfari, Davide; Fazio, Maria; Puliafito, Antonio; Villari, Massimo
Summary: Nowadays, remote desktop technologies are widely used to control remote computers. In this context, more and more Desktop as a Service (DaaS) solutions that allow users to directly control Virtual Machines through HTML5 web applications are emerging. However, currently, DaaS is at an early stage because several issues have to be addressed. In this paper, we aim to provide software architects a 360‐degree study on the major web‐based remote desktop client systems for the development of next generation DaaS solutions in both OpenStack‐based private and public Clouds. In particular, we compare and test different native and customized web‐based remote desktop solutions, specifically focusing on audio and video redirection performances in both Cloud environments. Exhaustive experiments highlight, from an objective point of view, the behavior of different DaaS solutions, providing useful hints to software architects and developers. Copyright © 2017 John Wiley & Sons, Ltd.